PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA BADAN PERENCANAAN, PENELITIAN DAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN MOROWALI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Pratama, Tulus (Katalogis, 2016)
The aims of this research are: 1) to test and analyze the influence of leadership style on work motivation in BAPPEDA of Morowali Regency; 2) to test and analyze direct influence of leadership styles on civil servants’ performance; 3) to test and analyze the influence of motivation on civil servants’ performance; 4) to test and analyze indirect influence of leadership styles on civil servants’ performance by using work motivation as an intervening variable. The type of this reseach is casual analysis that shows influential relationship between variables through the involvement of 39 respondents who are selected through purposive sampling method. Based on multiple linear regressionsanalysis test, it shows that leadership styles positively and significantly influence work motivation of civil servants in The Agency of Planning, Research, and regional Development of Morowali Regency; Leadership styles directly influence civil servants’ performance positively and significantly; work motivation positively and significantly influences civil servants’ performance; leadership styles have indirect influence on civil servants’ performance with motivation as intervening variable.